2014
DOI: 10.1111/maps.12293
|View full text |Cite
|
Sign up to set email alerts
|

The strength of regolith and rubble pile asteroids

Abstract: Abstract-We explore the hypothesis that, due to small van der Waals forces between constituent grains, small rubble pile asteroids have a small but nonzero cohesive strength. The nature of this model predicts that the cohesive strength should be constant independent of asteroid size, which creates a scale dependence with relative strength increasing as size decreases. This model counters classical theory that rubble pile asteroids should behave as scale-independent cohesionless collections of rocks. We explore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
179
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(194 citation statements)
references
References 48 publications
14
179
0
1
Order By: Relevance
“…In particular, lunar regolith has micron to centimeter sized grains described by an approximate d -3 size distribution 6,19 . Rubble pile asteroid (25143) Itokawa also has a d -3 grain size distribution but has boulders ranging up to ~40 m in size on the surface 20 , which is reflected in its much higher thermal inertia value of ~750 J m -2 K -1 s -1/2 (ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, lunar regolith has micron to centimeter sized grains described by an approximate d -3 size distribution 6,19 . Rubble pile asteroid (25143) Itokawa also has a d -3 grain size distribution but has boulders ranging up to ~40 m in size on the surface 20 , which is reflected in its much higher thermal inertia value of ~750 J m -2 K -1 s -1/2 (ref.…”
mentioning
confidence: 99%
“…To check whether internal cohesive forces are also required to prevent structural failure of 1950 DA, we applied the Drucker-Prager model for determining the failure stresses within a geological material 4,6 (Methods). In this model, the maximum spin-rate a rubble pile asteroid can adopt depends on its overall shape, degree of self-gravity, and internal strength.…”
mentioning
confidence: 99%
“…The boulders are pulled in opposite directions by a force increasingly stronger than their mutual gravitational attraction to measure the tensile strength of the bridge. This study [17] showed that the tensile strength of a cohesive aggregate is inversely proportional to the average particle size of the particles forming it (porosity, Hamaker constant, coordination number and others are considered constants). Basically, the smaller dust and regolith in an asteroid could be seen as a weak cement, a matrix in which the larger boulders are embedded.…”
Section: Granular Asteroids and Yorpmentioning
confidence: 99%
“…Time evolution of two selfgravitating granular bridge: (top) cohesionless and (bottom) cohesive. The latter needed a pulling force about 40 times greater than the one on top to fail catastrophically [17].…”
Section: Granular Asteroids and Yorpmentioning
confidence: 99%
“…Note that the actual value is actually closer to 45 µN/W due to the fact that the geometrical losses are in fact closer to 13% than 30% for the range of possible combinations between power and beam diameter covered in this specific example. Sánchez and Scheeres (2014) In order to put the surface velocity requirement into context, one can look at the asteroid spinning rate distribution in Figure 20. For asteroids larger than 1km, the spin limit is usually dominated by the gravity stresses and equates…”
Section: Constraints On the Laser Systemmentioning
confidence: 99%